427 The Effect of Malnutrition on Early Outcomes after Cancer Surgery: An International Prospective Cohort Study in 82 Countries. (4th May 2021) - Riad, A; Knight, S; Harrison, E
Abstract: Background: Malnutrition is a state linked to worse postoperative outcomes, and cancer patients are particularly vulnerable due to cachexia. We aimed to explore the effect of malnutrition on 30-day mortality following gastric and colorectal cancer surgery. Method: GlobalSurg3 was multicentre international cohort study which collected data from consecutive patients undergoing emergency or elective surgery for gastric and colorectal cancer. Malnutrition was defined using the Global Leadership Initiative on Malnutrition (GLIM) criteria. Multilevel variable regression approaches determined the relationship between malnutrition and early postoperative outcomes. Results: 6438 patients were included in the final analysis (1184 gastric cancer; 5254 colorectal cancer). Severe malnutrition was common across all income-strata, affecting 1 in 4 patients overall, with a higher burden in low and lower-middle income countries (64%). In patients undergoing elective surgery (n = 5709), severe malnutrition was independently associated with increased mortality (aOR = 1.62 (1.07-2.48, P = 0.024) after accounting for patient factors, disease stage and country effects. Conclusions: Severe malnutrition represents a high global burden in cancer surgery, particularly within lower income settings. Malnutrition is an independent risk-factor for 30-day mortality following elective surgery for gastric and colorectal cancer, suggesting perioperative nutritional interventions may improve outcomes after cancer surgery.